Efeito da dexametasona sobre a morfofisiologia testicular e cortical da adrenal em ratos wistar (Rattus norvegicus) - Rosa, Amarildo Marciano (2013)
This work was performed in the laboratories of animal reproduction, pharmacology and experimental surgery, university josé do rosário vellano-unifenas, in order to evaluate some aspects related to the morphological changes of cortical adrenal glands and testicles in rats treated with dexamethasone, an anti-inflammatory corticosteroid with immunosuppressive activity in the hypothalamic-pituitary-adrenal.The experiments were conducted to determine the hematological parameters, hormonal and functional morphology of the testicles and adrenal glands of wistar rats (Rattus norvegicus) submitted to dexamethasone at a dose of 40μg/100g weight by 3 days and 7 days of application. The groups were formed by 40 male wistar rats, adult, with average weight of 330g were divided into groups of 10 animals, 10 control and 10 treatment for 3 days and 10 control and 10 treatment for 7 days, where the group treatment received 0.07 ml of dexamethasone intramuscularly and the control group received 0.07 ml of saline intramuscularly. Data were expressed as mean ± standard error of mean (x ± sem), analyzed and compared using the student t-test, with significance level of 5% (p <.05). Were analyzed by the statistical package graphpad instat ® _, version 3.00 (graphpad software inc., san diego, california, usa). Significant differences were found between control and dexamethasone groups in hematological parameters (p <0.05), hormonal (p <0.05) and morphological (p <.05). There was no significant difference in spermiograms. It was concluded that the use of dexamethasone was responsible for the reduction in immune response with a significant lymphopenia, hormonal suppression of cortisol production by the adrenal glands atrophy of adrenal glands, and reduction in weight of the animals, representing the same catabolic effect on body. No interference in the structure of the testicles morphofunctional significantly, nor were there significant changes in the concentration of total testosterone.